Comparison of sleep quality among COVID-19 patients and non-COVID-19 population in Pakistan: A cross sectional study during the COVID-19 pandemic. (June 2022) - Malik, Muna; Atiq, Ayesha; Tahir, Muhammad Junaid; Akhtar, Fahd Kamal; Malik, Muhammad Irfan; Hassan, Wardah; Asad Khan, Fatima Muhammad; Akram, Iqra; Manhas, Noraiz; Ullah, Irfan; Asghar, Muhammad Sohaib
Abstract: Background: Adverse effects on the health and well-being changes may also express as a decreased sleep quality in COVID-19 patients. This study aimed to assess sleep quality among confirmed COVID-19 patients and the non-COVID-19 Pakistani population. Methods: An online cross-sectional survey was conducted between April and September 2020 in Punjab province, Pakistan. Information about demographic characteristics, COVID-19 diseased status, prior knowledge about COVID-19, and sleep quality using the Pittsburgh Sleep Quality Index (PSQI) was collected. Results: A total of 597 participants were included in this study, 296 (49.6%) COVID-19 patients and 301(50.4%) non-COVID-19 population. The PQSI was used to measure seven distinct sleep components; subjective quality, latency, duration, efficiency, disturbances, medication, and daytime dysfunction. Where mean ± standard deviation (SD) were 0.96 ± 0.743, 1.47 ± 1.032, 0.97 ± 1.006, 0.61 ± 0.995, 1.13 ± 0.649, 0.23 ± 0.651, 1.02 ± 0.861 respectively in total population (N = 597). Sleep latency, sleep duration, and sleep efficiency did not show a significant difference in the T-Test. While sleep quality, sleep disturbances, sleep medication, and daytime dysfunction showed a significant difference between both populations. Conclusion: In conclusion, we highlighted the poor sleep quality in COVID-19 patients as compared to the non-COVID-19 population. Highlights: This study highlighted the poor sleep quality in COVID-19 patients as compared to the non-COVID-19 population. Sleep latency, sleep duration, and sleep efficiency did not show a significant difference. We found that Sleep quality, sleep disturbances, sleep medication, and daytime dysfunction components showed a significant difference.